2020
DOI: 10.1210/jendso/bvaa009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethnicity on Outcomes of Diabetes Inpatient Hypoglycemia: an Australian Perspective

Abstract: Aims To evaluate outcomes of diabetic inpatient hypoglycemia among Aboriginal and Torres Strait Islander (ATSI) compared with Australian Caucasian patients. Methods A retrospective audit of diabetic patients aged > 18 years admitted at a regional hospital general ward between April 1, 2015, and March 31, 2016, was analyzed. The database contains clinical information at the time of admission and initial discharge and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Reports from international registries revealed that extended LOS was independently associated with a history of comorbidities such as diabetes, heart disease, and hypertension, which were correlated with improved selected outcomes [15,16]. Our ndings are in consistent with earlier reports that comorbidity is one of the risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Reports from international registries revealed that extended LOS was independently associated with a history of comorbidities such as diabetes, heart disease, and hypertension, which were correlated with improved selected outcomes [15,16]. Our ndings are in consistent with earlier reports that comorbidity is one of the risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Although conditions associated with a marked increase in hypoglycemia risk were excluded due to prior AMU stabilization, the patients with documented hypoglycemia accounted for 7.2% of all bed-days on the audited wards. This is greater than the estimated equivalent figure of 3.8% to 7.0% for all Australian inpatients with at least one documented BGL ≤3.9 mmol/L [6][7][8]. Most of the present patients experienced only a single episode, but a disproportionate number of events occurred overnight, most were not associated with typical symptoms, and approaching one third were Level 2.…”
Section: Discussioncontrasting
confidence: 58%
“…Patients with hypoglycemia contributed less to total bed days on the geriatric compared with the general medical wards. Because of their clinical complexity, general medical inpatients in the present audit were likely to have been older than in previous Australian studies [6,7]. Their relatively high hypoglycemia rate could reflect this since age is a recognized risk factor for inpatient hypoglycemia [3].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations